Military Migration and Demographic Transformations in Ukraine: Military Consequences for Territorial Communities - Karolyi, H.; Akimova, L. М.; Mishchuk, H. Yu.; Akimov, O. O.; Karpa, M. I. (Ukrainian Geographical Journal, 2025)
Population migration is one of the natural phenomena that occurs in society regardless of the form of social and economic system, and is considered within the framework and at the intersection of various sciences. However, military migration has its unique features and a distinct landscape of its processes, occurrences, and ongoing developments. The subject of this research is the complex of problems related to military migration in Ukraine, as well as its impact on the socio-economic development of territorial communities. The article aims to map both visible situations and latent processes in the territorial communities of Ukraine caused by military migration during the Russo-Ukrainian War. It is demonstrated that the consequences of military migration have both positive and negative aspects, thereby becoming a source of conflict and contributing to a decline in living standards within territorial communities. The need to combine the efforts of government bodies, civil society, and stakeholders in a comprehensive study of the consequences of military migration on communities is emphasized to develop effective models and strategies to overcome negative patterns. The fundamental issues surrounding military migration are reexamined to incorporate some of the significant new field data that has surfaced recently and to outline the policy implications of the results.
Keywords: internal migration; civil society; conflicts; military migration implications; communities resilience; social integration